2003
DOI: 10.1002/dc.10233
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology of chondroblastoma of soft parts: Case report and differential diagnosis with other soft tissue tumors

Abstract: Chondroblastoma is a benign tumor arising in the epiphysis of long bones. The extraskeletal presentation is most unusual. We report the first cytological description of a soft tissue chondroblastoma. It was a subcutaneous mass in the leg of a 62-yr-old man. Fine-needle aspiration (FNA) rendered a highly cellular material with grouped and single polygonal or round cells with a uniform, sometimes eccentric nucleus. Microvacuolated cytoplasm and hemosiderin pigment were frequent findings. There were rare nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…12,38,39 In general, chondroblastomas display low proliferative activity. 18,40 High mitotic activity, however, has been described by Ishikawa et al in an aggressively growing temporal bone chondroblastoma with a high MIB-1 index.…”
mentioning
confidence: 99%
“…12,38,39 In general, chondroblastomas display low proliferative activity. 18,40 High mitotic activity, however, has been described by Ishikawa et al in an aggressively growing temporal bone chondroblastoma with a high MIB-1 index.…”
mentioning
confidence: 99%
“…Some authors have claimed that the smears characteristically reveal hyper-to-hypocellular lobules comprised of small round-to-polyhedral cells (chondroblasts) embedded in an abundant myxoid stroma [17,18,19,20]. Granados et al [19] reported fine-needle aspiration findings of a soft tissue chondroblastoma in the leg of a 62-year-old man.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological features have been published in the literature concerning the diagnosis of chondroblastoma by AB [17,18,19,20]. Some authors have claimed that the smears characteristically reveal hyper-to-hypocellular lobules comprised of small round-to-polyhedral cells (chondroblasts) embedded in an abundant myxoid stroma [17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are rare at extraosseous, soft tissue locations. [56] An extraosseous intracranial location[7] for this bony tumor is a rare entity. We report a case of an intracranial intra-axial chondroblastoma in a young patient.…”
Section: Introductionmentioning
confidence: 99%